Environmental factors contributing to the convergence of bacterial community structure during indigo reduction - Farjana, Nowshin; Tu, Zhihao; Furukawa, Hiromitsu; Yumoto, Isao (Frontiers in Microbiology, 2023)
Indigo is solubilized through the reducing action of the microbiota that occurs during alkaline fermentation of composted leaves of Polygonum tinctorium L. (sukumo). However, the environmental effects on the microbiota during this treatment, as well as the mechanisms underlying the microbial succession toward stable state remain unknown. In this study, physicochemical analyses and Illumina metagenomic sequencing was used to determine the impact pretreatment conditions on the subsequent initiation of bacterial community transition and their convergence, dyeing capacity and the environmental factors critical for indigo reducing state during aging of sukumo. The initial pretreatment conditions analyzed included 60°C tap water (heat treatment: batch 1), 25°C tap water (control; batch 2), 25°C wood ash extract (high pH; batch 3) and hot wood ash extract (heat and high pH; batch 4), coupled with successive addition of wheat bran from days 5 to 194. High pH had larger impact than heat treatment on the microbiota, producing more rapid transitional changes from days 1 to 2. Although the initial bacterial community composition and dyeing intensity differed during days 2–5, the microbiota appropriately converged to facilitate indigo reduction from day 7 in all the batches, with Alkaliphilus oremalandii, Amphibacillus, Alkalicella caledoniensis, Atopostipes suicloalis and Tissierellaceae core taxa contributing to the improvement of when the dyeing intensity. This convergence is attributed to the continuous maintenance of high pH (day 1 ~) and low redox potential (day 2~), along with the introduction of wheat bran at day 5 (day 5~). PICRUSt2 predictive function profiling revealed the enrichment of phosphotransferease system (PTS) and starch and sucrose metabolism subpathways key toward indigo reduction. Seven NAD(P)-dependent oxidoreductases KEGG orthologs correlating to the dyeing intensity was also identified, with Alkalihalobacillus macyae, Alkalicella caledoniensis, and Atopostipes suicloalis contributing significantly toward the initiation of indigo reduction in batch 3. During the ripening period, the staining intensity was maintained by continuous addition of wheat bran and the successive emergence of indigo-reducing bacteria that also contributed to material circulation in the system. The above results provide insight into the interaction of microbial system and environmental factors in sukumo fermentation.